2013
DOI: 10.1007/s10815-013-9939-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, cytogenetic, and molecular analysis with 46,XX male sex reversal syndrome: case reports

Abstract: Purpose To investigate the clinical characteristics of different categories of sex-reversed 46,XX individuals and their relationships with chromosomal karyotype and the SRY gene. Methods Chromosome karyotyping for peripheral blood culture and multi-PCR and FISH were performed. Results Endocrinological data showed that their endocrine hormone levels were similar to that observed for Klinefelter syndrome, with higher FSH and LH levels and lower T levels. Chromosome karyotyping for peripheral blood culture reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…In a study involving 11 genetically proven XX male patients, the heights were between 160 and 165 cm with a mean of 161 cm, which matches the auxological findings of our patients. The appearance of the external genitalia of our patients are also identical to that particular cohort with normal masculinization and small testes [2].…”
Section: Discussionsupporting
confidence: 78%
“…In a study involving 11 genetically proven XX male patients, the heights were between 160 and 165 cm with a mean of 161 cm, which matches the auxological findings of our patients. The appearance of the external genitalia of our patients are also identical to that particular cohort with normal masculinization and small testes [2].…”
Section: Discussionsupporting
confidence: 78%
“…Screening of study titles and abstracts revealed 47 articles potentially eligible for inclusion; a further assessment based on the full-text led to the exclusion of 10 papers (Figure 1). The 37 selected studies described 64 adult patients with XX male syndrome [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Most patients (85%) were generally diagnosed after puberty during consultation being referred to a specialist because of hypogonadism, gynaecomastia and/or infertility. They have a normal male phenotype at birth (Gao et al., ). Approximately 15% of XX males had hypospadias, severe genital ambiguity or cryptorchidism (de la Chapelle, ).…”
Section: Discussionmentioning
confidence: 99%